2014
DOI: 10.1016/j.jgg.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan Modulation in Mice and the Confounding Effects of Genetic Background

Abstract: We are currently in the midst of a revolution in ageing research, with several dietary, genetic and pharmacological interventions now known to modulate ageing in model organisms. Excitingly, these interventions also appear to have beneficial effects on late-life health. For example, dietary restriction (DR) has been shown to slow the incidence of age-associated cardiovascular disease, metabolic disease, cancer and brain ageing in non-human primates and has been shown to improve a range of health indices in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 95 publications
(137 reference statements)
1
27
0
Order By: Relevance
“…Like DAF-16 in C. elegans, FoxO transcription factors together with calorie restriction and insulin signaling have been reported to regulate lifespan in rodents (Mulvey et al, 2014;Shimokawa et al, 2015). For example, decreased insulin signaling correlates with human longevity (Kojima et al, 2004;Pawlikowska et al, 2009), as do several genetic variants in FOXO3 (Willcox et al, 2008;Pawlikowska et al, 2009;Flachsbart et al, 2009;Li et al, 2009).…”
Section: Foxo In Mammalian Longevitymentioning
confidence: 99%
“…Like DAF-16 in C. elegans, FoxO transcription factors together with calorie restriction and insulin signaling have been reported to regulate lifespan in rodents (Mulvey et al, 2014;Shimokawa et al, 2015). For example, decreased insulin signaling correlates with human longevity (Kojima et al, 2004;Pawlikowska et al, 2009), as do several genetic variants in FOXO3 (Willcox et al, 2008;Pawlikowska et al, 2009;Flachsbart et al, 2009;Li et al, 2009).…”
Section: Foxo In Mammalian Longevitymentioning
confidence: 99%
“…In contrast, a 33% increase in lifespan was observed when this mutation was expressed on the short-living 129 background. In addition, the underlying impact of the strain on stress resistance may also be in play (81). In general, much of these data (53) GH, growth hormone; GHRHR, growth hormone-releasing hormone receptor; Tg, transgenic; IGF-IR, IGF-I receptor; ND, not determined; GHRKO, GH receptor knockout; FGF21, fibroblast growth factor 21; LID, liver IGF-I ablated; iLID, inducible liver-specific IGF-I knockout; FIRKO, fat insulin receptor knockout; ␣-MUPA, ␣-mouse urokinase-type plasminogen activator; Papp-A, pregnancy-associated plasma protein-A.…”
Section: Interventions That Alter Gh or Igf-i)mentioning
confidence: 99%
“…Empirical evidence has existed for over a century that dietary restriction (DR) increases lifespan and healthspan across multiple species (Fontana and Partridge 2015;Picca et al 2017;Weindruch and Walford 1988). In mice, significant strain-specific differences in lifespan exist (Turturro et al 1999;Yuan et al 2009) and genetic background may consequently play an important but under-appreciated role in how particular strains respond to DR (Hempenstall et al 2010;Ingram and de Cabo 2017;Mitchell et al 2016;Mulvey et al 2014;Selman and Swindell 2018;Swindell 2012). For example, two independent studies have reported that recombinant inbred ILSXISS mice show significant strain-specificity in longevity following 40% DR (Liao et al 2010;Rikke et al 2010), and phenotypic parameters linked to the ageing process, such as in mitochondrial function and adiposity, have been shown to differ between ILSXISS strains under 40% DR (Liao et al 2011;Mulvey et al 2016).…”
Section: Introductionmentioning
confidence: 99%